State Control, User Experience, and Purchase Intentions in the Digital Economy: Empirical Evidence from Vietnam - Huynh Minh, Sang; Phan Nhan, Trung (PT. Riset Press International, 2025)
The rapid growth of digital commerce has reshaped consumer behavior, highlighting the role of state control, social media interaction (SMI), and user experience (UX) in influencing purchase decisions (PD). This study explores how government policies and regulations on digital platforms influence user engagement and online experiences, influencing purchase behavior. Drawing on institutional theory, the theory of planned behavior (TPB), and the unified theory of acceptance and use of technology (UTAUT2), the study develops and tests a conceptual model linking these factors. Data were collected from a quantitative survey of social media users in Vietnam and then analyzed using structural equation modeling (PLS-SEM). The results show that state control does not directly affect shopping behavior but mainly indirectly through social media interaction and user experience. At the same time, user experience plays the most important role in driving purchase decisions, emphasizing the importance of convenience, trust, and satisfaction when using digital platforms. In terms of practical applications, the study recommends that businesses optimize customer experience through intuitive and personalized digital interfaces based on AI while encouraging participation and interaction on the platform. The government must focus on building a safe digital ecosystem, strengthening the legal framework, and supporting small and medium-sized enterprises (SMEs) to participate in e-commerce. This study contributes to the literature by integrating state control as a factor influencing consumer behavior while providing useful, practical suggestions for policymakers and digital marketing strategies.